Apa Itu Ekonomi dan Mengapa Kita Membutuhkannya? - Heri Sukendar Wong (Bina Nusantara University, 2011)
This paper aims to explain what the problems of modern society in meeting the necessities of life and efforts in improving their welfare. Determination of the wrong economic policies undertaken by a group of people will result in suffering for the people themselves, and even spread to other communities where the economic linkages between groups of people so closely with one another. The economic crisis experienced in the United States that occurred in the year 2007 till now influent to other countries. Economic problems arise because of scarcity, which resulted in the society should allocate its resources efficiently and optimally. The differences of geography, talent and expertise of community groups demanding to produce goods and services into its superiority. Raises production specialization trade, and commerce will take place efficiently with the help of money. Everything is dedicated to improving the welfare of society itself.